STRATEGI PEMBANGUNAN BERKELANJUTAN DI KAWASAN PERBATASAN DAN PERKOTAAN TANJUNG BALAI KARIMUN - Muhammad Thaha Yasin Ramadhan; Asa Bintang Kapiarsa; Tiuridah Silitonga; Yurika Afrianita; Siska Kurnia Novianty; Normasela; Tesiherdawati; Ika Putri Ramadani Lailatul Shima (JURNAL PELITA KOTA, 2023)
The new direction in the current development process is through the implementation of the Sustainable Development Goals (SDGs)/ Tujuan Pembangunan Berkelanjutan (TPB) to remote areas, border areas and also underdeveloped areas. One of the border areas that is undergoing significant development in Indonesia is Karimun Regency. Karimun Regency is one of the areas in the Riau Archipelago Province that exercises with Singapore and Malaysia. The development center of Karimun Regency itself is in the Tanjung Balai Karimun Urban Area. This area can be a trigger for sustainable development in other border areas. So, the purpose of this research was develop a strategy for developing TPB in Tanjung Balai Karimun Urban Areas using a SWOT analysis. The research method used in this research is by using a qualitative descriptive analysis method. This resulted in 30 main TPB strategies that needed to be further developed in the Tanjung Balai Karimun Urban Area.